The Missing Dynamic: Corporations, Individuals and Contracts - Iyer, Arun A. (Journal of business ethics, 2006)
There are two opposing views on the nature of corporations in contemporary debates on corporate social responsibility. Opponents of corporate personhood hold that a corporation is nothing but a group of individuals coming together to achieve certain goals. On the other hand, the advocates of corporate personhood believe that corporations are persons in their own right existing over and above the individuals who comprise them. They talk of corporate decision-making structures that help translate individual decisions and actions into corporate decisions and actions. Importantly both the advocates and the opponents of corporate personhood rely on a contractual model of corporate–social interaction to explain corporate social responsibilty. However, this contractual model misses crucial aspects of the relationship between corporations and societies. Economic history reveals that the relationship between corporations and societies is essentially dynamic and heterogeneous and so extremely difficult to characterise in terms of a contract. The economic and the political aspects of this relationship are so finely intertwined with each other and it is impossible to extricate the one from the other. We need to be more conscious of the actual nature of corporate–social interaction in order to deal more comprehensively with issues of corporate social responsibility.